The Influence of the Course Review Horay (CRH) Model on the Learning Outcomes of Grade X Students in Sociology Subjects at MAN 1 Trenggalek - Linda Maulana Nabila; Bagus Setiawan (International Journal of Technology and Education Research, 2026)
This research is motivated by the low learning outcomes of students in Sociology class X at MAN 1 Trenggalek, which is indicated by the suboptimal achievement of cognitive competencies, low student participation in learning, and the dominant use of conventional methods. The Course Review Horay (CRH) learning model was chosen as an alternative to cooperative learning that emphasizes active involvement, a pleasant learning atmosphere, and strengthening conceptual understanding through material review activities. The purpose of this study is to analyze the differences in learning outcomes of students who take part in learning using the CRH model and students who learn using conventional methods, and to describe student responses to the application of the model. The study uses a quantitative approach with a quasi-experimental design. The research sample was determined through a purposive sampling technique with class XG as the experimental class and class XB as the control class. Data collection was carried out through pre-tests, post-tests, and questionnaires. Data analysis used the Independent Samples T-Test. The results showed a significant difference between student learning outcomes in the experimental class and the control class. The calculated t value of 5.328 is greater than the t table of 2.002 with a significance of 0.000 (p < 0.05). The Mean Difference value is 11.159 and the difference in N-Gain effectiveness reaches 28.89%. Student responses to the application of the CRH model are in the very high category with a percentage of 82.32%. These findings indicate that the Course Review Horay learning model has a positive effect on the Sociology learning outcomes of class X students of MAN 1 Trenggalek.